Analysis of Good Corporate Governance (GCG) at Amil Zakat Institutions: Analisis Good Corporate Governance (GCG) Pada Lembaga Amil Zakat - Moch Yusuf Bachtiar; Imelda Dian Rahmawati (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative study examines the financial reporting practices and application of Good Corporate Governance (GCG) principles within an Amil Zakat institution located in Surabaya, Indonesia. Using a descriptive approach, the study analyzes data collected through various techniques, including data collection, grouping, focus, presentation, and conclusion drawing. The results reveal that the implementation of the four key principles of GCG within the institution is commendable, contributing to improved company performance. Moreover, the institution provides monthly financial reports and transparently distributes zakat through their official website. This study underscores the significance of financial reporting and GCG as essential components for organizational success and accountability, providing implications for both academic research and global Zakat-related institutions. Highlights: Enhanced accountability: The study explores how financial reporting and the application of Good Corporate Governance (GCG) principles contribute to increased accountability within an Amil Zakat institution. Transparency and accessibility: The research highlights the institution's practice of providing monthly financial reports and making zakat distribution information accessible through their official website, promoting transparency in operations. Implications for organizational performance: The findings emphasize the positive impact of effective financial reporting and GCG implementation on overall company performance, underscoring the importance of these practices in achieving organizational goals. Keywords: Financial reporting, Good Corporate Governance (GCG), Amil Zakat Institution, Qualitative study.